Drug use by elderly inpatients of a philanthropic hospital - Rômulo Moreira dos Santos; Ivana Maria Fechine Sette; Lindomar de Farias Belém (Universidade de São Paulo, 2011)
The high incidence of chronic diseases in the elderly leads to increased intermittent drug therapies. The presence of concomitant diseases and prescriptions made out by various health professionals facilitate the practice of polypharmacy, the emergence of iatrogenic diseases, and therapeutic regimens that are inconvenient for patients. The present study was carried out among elderly patients hospitalized at the Hospital Care Foundation of Paraiba, Campina Grande, with the objectives of studying the consumption of drugs by these patients, noting the possible adverse drug reactions (ADR), drug interactions and the presence of high-risk drugs prescribed to this age group. The study had a descriptive and cross-sectional quantitative design and involved a sample of 65 patients accompanied by the Pharmacovigilance Centre of the hospital, from August 2009 to July 2010. Over 90% of the patients were on polypharmacy, and the possible ADR found were related to the gastrointestinal tract where the most frequent interactions were with cardiovascular drugs. Within the context of pharmacoepidemiology, pharmacists can contribute by improving the quality of life of patients and preventing unnecessary expense with erroneous and poorly evaluated treatments. A elevada incidência de doenças crônicas na terceira idade induz ao aumento de terapias medicamentosas intermitentes. A presença de patologias concomitantes e prescrições elaboradas por diversos profissionais de saúde facilitam a prática da polifarmácia, surgimento de doenças iatrogênicas e esquemas terapêuticos pouco cômodos para o paciente. O estudo foi realizado junto aos pacientes idosos internados no Hospital da Fundação Assistencial da Paraíba (FAP), Campina Grande, com objetivo de estudar o consumo de medicamentos por estes pacientes, observando as possíveis reações adversas a medicamentos (RAM), interações medicamentosas apresentadas e a presença de medicamentos de alto risco prescritos para este grupo etário. A pesquisa foi descritiva e transversal, com abordagem quantitativa, constituída por uma amostra de 65 pacientes, acompanhados através do Centro de Farmacovigilância do hospital, no período de agosto de 2009 a julho de 2010. Mais de 90% dos pacientes estavam sob polifarmácia, as possíveis RAM encontradas estavam mais relacionadas ao trato gastrintestinal e as interações foram mais frequentes com os medicamentos de ação cardiovascular. Dentro do contexto da farmacoepidemiologia, o profissional farmacêutico pode contribuir para a melhoria da qualidade de vida dos pacientes e evitar gastos desnecessários devido à terapêuticas errôneas e mal avaliadas.